One Pot Synthesis of Alkyl Nitriles - Umesh Patil; Bharat Sonawane; Balaji Madje; Sayujjata Vaidya (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
A one-pot synthesis method to produce alkyl nitriles using the corresponding aliphatic carboxylic acid has been developed. The process involves treating the aliphatic acid with thionyl chloride to obtain the corresponding aliphatic acid chloride, which is then further treated with anhydrous ammonia gas to yield the respective aliphatic acid amide. The intermediate corresponding amide is dehydrated with thionyl chloride to obtain alkyl nitrile with a quantitative yield.
Keywords: Alkyl Nitriles; Ammonia; Aliphatic Carboxylic Acid Chloride; Aliphatic Carboxylic Amide